The Dialectics of Global Justice From Liberal to Postcapitalist Cosmopolitanism. - Sculos, Bryant William (SUNY Series in New Political Science Ser., 2022)
Draws on Marx and the first-generation Frankfurt School to make the case that cosmopolitanism must become a postcapitalist political theory.